Combining superficial and deep lymphovenous anastomosis for lymphedema treatment: Preliminary results. Issue 1 (4th January 2021) - Scaglioni, Mario F.; Meroni, Matteo; Fritsche, Elmar
Abstract: Background: Superficial lymphovenous anastomosis (LVA) is a widely accepted procedure for treatment of mild‐to‐moderate lymphedema throughout the body. Anyway, not always are the superficial lymphatic vessels suitable for the anastomosis nor do they provide a sufficient drainage to significantly improve the condition. The continuous progress of supermicrosurgical technique over the last few years and the recent anatomical researches about the deep lymphatic network opened new perspectives for those lymphedema cases refractory to conventional procedures. Resorting to deep lymphatic vessels offer an additional opportunity to further improve the result obtained by means of superficial LVA. The aim of this report is to describe our experience treating lymphedema with superficial and deep lymphatic vessels LVA. Patients and Methods: Eight female patients presenting secondary (seven cases) and primary (one case) lymphedema, previously treated by means of multiple superficial LVAs, were considered eligible for deep lymphatics surgery to further improve their results. The affected area was the upper limb in one case and the lower limbs in seven cases. All the patients were evaluated preoperatively and postoperatively resorting to Campisi criteria. Four cases were initially classified as stage III, two stage IV, and two stage II. Five patients received deep LVA in the groin, two patients in the ankle along the posterior tibial artery and one in the wrist along the radial artery. Results: In all eight patients both subjective and objective improvements of the condition were reported with decrease of swelling and relief from heaviness sensation. The postoperative course was always uneventful and at the 9 months follow up none of the patients presented recurrence of the disease, even with the complete removal of compressive therapy. Conclusions: Deep lymphatic vessels LVA might represent a valid alternative to the superficial ones to treat lymphedema when previous results are not satisfactory nor when no superficial lymphatic vessels are available for anastomosis.